Using an Incremental Testing Strategy to Improve Students’ Perception of Software Quality - Santos, Italo; Mori, Allan; Souza, Simone R. S. (Anais do Workshop sobre Educação em Computação (WEI); 2021: Anais do XXIX Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2021.15909, 2021)
Teaching software testing should include a broad view of the main techniques, criteria, and tools. In general, students have few opportunities to test their code-projects suitably during the undergraduate course and, therefore, teaching software testing in practice is crucial to students recognize the advantages and limitations of different testing techniques. This paper reports the experience of teaching software testing in practice, with students applying an incremental testing strategy to validate their software projects. Students selected a software project developed during their undergraduate and an incremental testing strategy, including testing criteria learned in the class. The students should choose the testing techniques, apply them and write a report with the results and perceptions. Through this experience, it was possible to show to the students, in practice, the importance of combining more than one technique during the software testing activity.